Pattern of Neonatal Intestinal Obstruction in a Tertiary Care Hospital and its Management: A Prospective Study - Laxmikanta Mohapatra; Prasanta Kumar Tripathy; Pradeep Kumar Jena; Hiranya Kishor Mohanty (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Intestinal obstructions are the most common conditions in neonates, requiring emergency surgical intervention. The management and outcome are challenging particularly in a developing country. Aim: To find the pattern of neonatal intestinal obstruction, the management approach and outcome in a paediatric surgery centre in Eastern India. Materials and Methods: This prospective cohort study was conducted in Department of Paediatric Surgery of SVP Postgraduate Institute of Paediatric, SCB Medical College, Cuttack, Odisha, India. It was conducted over a period of two years from October 2016 to September 2018. Patients with oesophageal atresia and anorectal malformation were excluded from the study. Results: Out of 126 newborns included in the study, intestinal atresia (56 cases) was the leading cause of obstruction and was found most commonly at the level of jejunum. A case of pyloric atresia associated with epidermolysis bullosa, a case of apple-peel type of intestinal atresia associated with jejunal duplication cyst and a case of colonic atresia associated with anorectal malformation were rare findings detected in the study. Hirschsprung's disease was the second most common pathology, found in 42 cases. Laparotomy, levelling biopsy and colostomy was done in all cases of Hirschsprung's disease. Malrotation (14 cases) and Meconium ileus (12cases) were also important causes of neonatal intestinal obstruction. Fourteen cases (11.1%) died during hospitalisation and septicaemia was the common cause of morbidity and mortality. Conclusion: Intestinal atresias are the most common cause of neonatal intestinal obstruction in our study (44% cases) followed by Hirschsprung's disease (33% cases). Male newborns were more commonly affected and majority of neonates presented during first week of life. Post-operative septicaemia, pneumonia and wound infection should be adequately managed. Early recognition of the problem and referral from peripheral hospitals in recent years were important for improved survival (89%) in the present study. Urgent resuscitation, diagnosis, surgical intervention and utmost utilization of available neonatal supporting system are the key factors.